The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2196/27010
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Leap of Faith: A Study of Abruptly Transitioning an Undergraduate Medical Education Program to Distance-Learning Owing to the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has forced universities worldwide to immediately transition to distance-learning. Although numerous studies have investigated the effect of the COVID-19 pandemic on universities in the Middle East, none have reflected on the process through which medical education programs for health professions underwent this transition. This study aimed to elucidate the rapid transition to distance-learning of an undergraduate medical program at the College of Medicine, Mohammad Bin Rashid University of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Internationally, the implementation of educational technology varies, with some markets, including the Middle East, having lower penetrance and lower public acceptance [ 12 , 13 ]. The literature is ripe with examples both supporting e-learning for medical education citing student benefits such as flexibility and increased student control but also noting concerns about use of e-learning for acquisition of clinical skills [ 14 17 ]. Others have presented a comparative analysis of online versus conventional learning that found that conventional teaching was preferred by students [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, the implementation of educational technology varies, with some markets, including the Middle East, having lower penetrance and lower public acceptance [ 12 , 13 ]. The literature is ripe with examples both supporting e-learning for medical education citing student benefits such as flexibility and increased student control but also noting concerns about use of e-learning for acquisition of clinical skills [ 14 17 ]. Others have presented a comparative analysis of online versus conventional learning that found that conventional teaching was preferred by students [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors suggested that educational institutions must make an informed decision and identify their explicit needs when deciding and choosing the most appropriate digital assessment platforms. Moreover, Du Plessis et al. (2021) stated that the COVID-19 pandemic has forced universities worldwide to immediately transit to distance learning and indicated the need for a web-based assessment.…”
Section: Resultsmentioning
confidence: 99%
“…MBRU is one of 8 medical colleges in the UAE and one of two in Dubai. MBRU was established in 2016, and currently offers a 6-year Bachelor of Medicine, Bachelor of Surgery (MBBS) program [ 10 , 30 , 31 ] as well as postgraduate degrees in dentistry [ 11 , 32 , 33 ], nursing, and biomedical sciences. The first 3 years of the respective MBBS program are preclinical and the remaining years are spent in the clinical setting.…”
Section: Methodsmentioning
confidence: 99%